Zingiber officinale preserves testicular structure and the expression of androgen receptors and proliferating cell nuclear antigen in diabetic rats. (5th February 2020) - Al‐Shathly, Mona Ramadan; Ali, Soad Shaker; Ayuob, Nasra Naeim
Abstract: The aim of this study was to assess the efficacy of Zingiber officinale, commonly referred to as ginger, in preserving the structural integrity of testis in streptozotocin (STZ)‐induced diabetic rats compared to the efficacy of metformin, the traditional effective antidiabetic drug. STZ was utilised for the induction of diabetes mellitus in male Sprague Dawley rats. The study included five groups ( n = 6 each), namely the normal control, ginger‐treated normal, nontreated diabetic, metformin‐treated diabetic and ginger‐treated diabetic groups. Biochemical assessment of fasting blood glucose level (BGL) and total antioxidant capacity (TAC) was performed. Histopathological assessment of the testes was performed using routine and immunohistochemical techniques. Fasting BGL significantly ( p = .01) reduced, whereas TAC significantly increased ( p < .001) in metformin‐ and ginger‐treated diabetic rats compared to those in untreated diabetic rats. Metformin and ginger reduced the degenerative changes observed in the testes of diabetic rats, significantly reduced ( p < .001) caspase‐3 immunoexpression, and significantly increased ( p < .001) the immune‐expression of androgen receptors and proliferating cell nuclear antigen. Ginger has antidiabetic effects and preserves testicular structural integrity and, thus, is recommended as an adjuvant therapy for male diabetic patients in the reproductive period.